Status of Members' Education and Training in the Co-operatives of Ilam - Thapa, Bhupal Krishna (Journal of Advanced Academic Research, 2015)
Cooperative is an organization run by the similar professional people for the betterment of their socio-economic uplift with common goals in the democratic way. The success or failure of any cooperative depends upon the members' role. If the members are well educated about cooperatives and have sound knowledge of their business, it is the true path to success. The present study was conducted to explore the status of cooperative member education and training to the members by the concerned cooperative in Ilam, Nepal. The nature of the study was quantitative survey method. There were 226 cooperative members from three types of cooperatives: Savings and Credit, Tea, and Dairy cooperatives. The present study showed that the majority of the members were deprived of their basic rights of getting cooperative members’ education and training from their concerned cooperatives. Thus, the study recommends that cooperatives must requested to provide their members with education and business oriented training.Journal of Advanced Academic Research Vol.1(1) 2014: 43-45